Review on Millimeter Wave Antenna for Future 5G Device - Sneha , Kamani; Agarwal , Vipul (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Millimeter-wave communications have demonstrated a promising future and are considered to be an appealing method in 5G fifth-generation wireless communication systems because of the rapid expansion of wireless data traffic.Moreover, to construct strong communication structures, understanding the channel dynamics in time and space at these frequencies is critical.Millimeter wave signals are particularly susceptible to blocking and because of their low signal attenuation, they have restricted communications abilities when particularly in comparison to microwave signals.Specifically, various designs from current papers are selected depending on their appealing features that assist 5G requirements and applications.In the mm-wave range, a T-shaped antenna can have a broad frequency range, including frequencies in the Ka-band such as 26.5 GHz to 40 GHz.Because ofits several benefits the PET substrate was chosen, including high flexibility,low cost, human body protection, and protection to environmental consequences. This review presents similar other mm-wave antenna array designs, and their strategies and challenges are discussed which are utilized to address the path loss that is unfavorableand mm-wave application blockage problems, which establish future directions.